2019
DOI: 10.17576/jsm-2019-4809-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Human Amniotic Membrane as a Scaffold for Periodontal Ligament Fibroblast Attachment and Proliferation

Abstract: This study was aimed at evaluating the ability of the human amniotic membrane (HAM) to act as a scaffold for the growth of the main cells in periodontal regeneration, human periodontal ligament fibroblasts (HPDLFs). The HAM has many biological properties that are suitable for periodontal tissue regeneration such as low immunogenicity, anti-fibrosis, anti-inflammation, and a rich extracellular matrix component. Commercially available HPDLFs were seeded onto the HAM, and the attachment and proliferation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Seven studies on GTR demonstrated that AM was an effective barrier able to enhance bone fill and improve periodontal parameters (probing pocket depth [PPD] and clinical attachment loss [CAL]). One laboratory study reported AM as a suitable scaffold for periodontal fibroblast cell growth [11]. The findings from all selected studies are summarized in Table 1.…”
Section: Figure 1: Flowchart Of the Literature Search And Selection P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies on GTR demonstrated that AM was an effective barrier able to enhance bone fill and improve periodontal parameters (probing pocket depth [PPD] and clinical attachment loss [CAL]). One laboratory study reported AM as a suitable scaffold for periodontal fibroblast cell growth [11]. The findings from all selected studies are summarized in Table 1.…”
Section: Figure 1: Flowchart Of the Literature Search And Selection P...mentioning
confidence: 99%
“…Consequently, it is a readily available and cost-effective biomaterial for scaffolds in tissue engineering [10]. Scanning electron microscopy analysis of AM revealed rough surface architecture with the presence of microporosity, which may provide a suitable platform for cell attachment [11]. AM was used for wound treatment more than a century ago as a skin graft substitute for open wound for treating burnt and ulcerated skin surfaces by which it can accelerate epithelialization and reduce pain [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…40 Through the advancement in clinical and laboratory techniques, HAM is now being used as a membrane in guided tissue regenerative procedures, substrate for culturing stem cells and as scaffolds for delivering regenerative cells into oral defects (Table 4). 11,14…”
Section: Medical and Dental Applications Of Human Amniotic Membranesmentioning
confidence: 99%
“…Nevertheless, with the current findings on the superiority of HAM histologically as well as clinically that are comparable with the current, available scaffolds for tissue engineering is a promising, alternative biomaterial in the management of periodontal defects. 14,22,36…”
Section: Potential Of Ham As a Substrate Or Scaffold In Periodontal mentioning
confidence: 99%
See 1 more Smart Citation